Interplay of Artificial Intelligence with Platform Engineering and Service Automation: A Perspective from an Enterprise Cloud Architect - Baba Prasad Pendyala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the dynamic interplay between Artificial Intelligence, Platform Engineering, and Service Automation from an Enterprise Cloud Architect’s perspective. It explores how cloud architects leverage AI technologies to transform cloud infrastructure design, management, and automation processes while navigating the technical complexities of modern enterprise environments. The discussion expands to cover the technical frameworks enabling human-AI collaboration in platform engineering, emphasizing the architectural patterns and implementation strategies that facilitate effective service automation. Through a detailed healthcare case study, the article demonstrates how an AI-augmented cloud platform revolutionizes patient diagnosis and treatment recommendation systems, highlighting the technical architecture, data integration challenges, and measurable clinical outcomes. It elaborates on governance structures, technical guardrails, and decision-making models essential for responsible AI implementation in enterprise cloud environments. Finally, this article identifies emerging technologies, architectural patterns for scaling human-AI synergy, and technical recommendations to guide enterprise cloud architects through the evolving landscape of AI-driven platform engineering and service automation.